The economic consequences of ageing: the case of Finland - de la Maisonneuve, Christine; André, Christophe; Garcia, Clara; Koen, Vincent (Paris, 2014)
"Finland’s population is set to age rapidly in the coming decades. This will put pressure on public finances, while shrinking labour resources. Nonetheless, solutions exist to alleviate those pressures. Adjusting the pension age in line with the rise in life expectancy would reduce pension costs and increase older workers’ employment, provided it is accompanied by the removal of the pathways to early retirement. In order to allow people to work longer, labour market flexibility should be enhanced and lifelong training promoted further. Active labour market policies should be strengthened so as to increase the labour force participation of youth, childbearing age women and the long-term unemployed. Finally, ageing should not only be seen as a burden as it can also create opportunities for innovation and new markets and industries. Information and communications technologies, where Finland has a strong knowledge base, can help the elderly stay as autonomous as possible, which would contain long-term care costs and improve well-being. This Working Paper relates to the 2014 OECD Economic Survey of Finland (www.oecd.org/eco/surveys/economicsurvey- finland.htm)."